2020
DOI: 10.1088/1361-6382/aba5ab
|View full text |Cite
|
Sign up to set email alerts
|

First law of black hole mechanics with fermions

Abstract: In the last few years, there has been significant interest in understanding the stationary comparison version of the first law of black hole mechanics in the vielbein formulation of gravity. Several authors have pointed out that to discuss the first law in the vielbein formulation one must extend the Iyer–Wald Noether charge formalism appropriately. Jacobson and Mohd (2015 Phys. Rev. D 92 124010) and Prabhu (2017 Class. Quantum Grav. 34 035011) formulated such a generalisa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The validity of Iyer and Wald's prescription has subsequently extended to theories that include fields with gauge freedoms in refs. [28][29][30], but the Heterotic Superstring effective action (and many other string effective actions) include a field which is not a connection or a section of some gauge bundle: the Kalb-Ramond field. This complication has been ignored in most of the string literature 3 and the Iyer-Wald prescription has been naively applied with results that seem to be compatible with the microscopic calculations of the entropy.…”
Section: Jhep10(2020)097mentioning
confidence: 99%
“…The validity of Iyer and Wald's prescription has subsequently extended to theories that include fields with gauge freedoms in refs. [28][29][30], but the Heterotic Superstring effective action (and many other string effective actions) include a field which is not a connection or a section of some gauge bundle: the Kalb-Ramond field. This complication has been ignored in most of the string literature 3 and the Iyer-Wald prescription has been naively applied with results that seem to be compatible with the microscopic calculations of the entropy.…”
Section: Jhep10(2020)097mentioning
confidence: 99%
“…There, we first focus on BF theory, and then introduce Einstein-Cartan (-Holst) gravity (ECH) as a constrained BF theory. As it turns out, the superficial analysis of the corner symmetries of tetrad gravity, which we recall in section 3.2, reveals the algebra diff(S) sl(2, C) S , where the sl(2, C) is due to internal Lorentz symmetries, and the boost component sl(2, R) ⊥ is absent (this last observation was first noted in [61] and further analyzed in [55,[62][63][64]). Compared with the metric case, much more work is required in order to decompose the potential of Einstein-Cartan-Holst gravity in terms of the fundamental bulk piece θ GR and a corner potential.…”
Section: Canonical General Relativity (Gr)mentioning
confidence: 82%
“…The combined transformation is sometimes referred to as Kosmann derivative in the literature; see e.g. [14][15][16][17], where it was shown that this prescription correctly reproduces the metric Noether charges for any diffeomorphism, and the metric Hamiltonian charges for isometries (see also [10,18]). For asymptotic symmetries at spatial infinity, the metric Hamiltonian charges (namely the Poincaré charges) are reproduced using either the Kosmann or the standard Lie derivative variations: their difference vanishes in the limit [9,19,20].…”
Section: Jhep12(2020)079mentioning
confidence: 99%
“…But the difference of the symplectic potentials by an exact 3-form remains, therefore this dual contribution is inequivalent to the one computed using tetrad variables. For the related topic of the contribution of torsion to the first law of black hole mechanics, see [18,26].…”
Section: Jhep12(2020)079mentioning
confidence: 99%